"Parabenoia" Debunked, or "Who's Afraid of Parabens?". Issue 6 (November 2015) - Sasseville, Denis; Alfalah, Maisa; Lacroix, Jean-Philip
Abstract : Parabens have been used as preservatives in foods, injectables, and topical preparations for nearly 10 decades. Present in nature, rapidly metabolized by skin and liver enzymes, they have an excellent safety record. However, in the past 15 years, they have been under scrutiny for their alleged estrogenic and antiandrogenic effects, as well as their putative role in promoting cancerogenesis through endocrine disruption. Scientific articles supporting these assertions have led the European Community to ban or restrict the use of some parabens. Despite that methylparaben and ethylparaben have negligible endocrine disruption activity, the food, pharmaceutical, and cosmetic industries are under pressure from scare campaigns in the media and are responding by replacing parabens with other biocides that cause multiple cases, and even worldwide epidemics, of allergic contact sensitization. In the present review, we present a balanced account of the published literature about the metabolism and potential toxicology of parabens.